Brolucizumab-Associated Intraocular Inflammation in Eyes Without Retinal Vasculitis. (July 2021) - Witkin, Andre J.; Hahn, Paul; Murray, Timothy G.; Arevalo, J. Fernando; Blinder, Kevin J.; Choudhry, Netan; Emerson, Geoff G.; Goldberg, Roger A.; Kim, Stephen J.; Pearlman, Joel; Schneider, Eric W.; Tabandeh, Homayoun; et al.
Purpose: This work analyzes a series of eyes with brolucizumab-associated intraocular inflammation (IOI) without retinal vasculitis reported to the American Society of Retina Specialists. Methods: The American Society of Retina Specialists Research and Safety in Therapeutics Committee analyzed clinical characteristics from submitted reports of IOI after brolucizumab. Eyes with retinal vasculitis or that received intraocular antibiotics were excluded. Results: Forty-nine eyes of 45 patients were collected. Mean visual acuity (VA) at baseline was 20/49 (range, 20/20-5/200). Patients presented with IOI a mean of 24 days (range, 3-63 days) after their most recent brolucizumab injection; 61% presented for an unscheduled visit while 39% presented at routine follow-up. Mean VA at IOI presentation was 20/67 (range, 20/20-3/200). The most common symptoms were floaters (78%) and blurry vision (76%). Pain (20%) and redness (16%) were less common; 3 (6%) eyes were asymptomatic. IOI was anterior only in 18%, posterior only in 31%, and both anterior and posterior in 51% of eyes. Treatment included topical steroids alone in 67% of eyes, whereas 10% of eyes received no treatment. Mean VA at last follow-up was 20/56 (range, 20/20-1/200). Three (6%) eyes lost 3 or more lines and 1 (2%) eye lost 6 or more lines. Conclusions: Brolucizumab-associated IOI without retinal vasculitis typically presented with a delayed onset of a few weeks. Often, VA decline was relatively mild. Most symptoms resolved and nearly all had a return-to-baseline VA, but a small percentage of patients had a significant decrease in VA at last follow-up.